Nilai Pendidikan Karakter Anak dalam Antologi Cerita Remaja Tarian Salju Karaban - Ichwan Arif (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
This study describes the value of character education of children in the anthology of adolescent story Tarian Salju Karaban. This paper will discuss some of short stories from 15 short stories in the anthology, namely the Snow Dance Keraba (TSK) by Aulal Muna, Tembang Canting Kinanti (TCK) by Khalisha Hamida, Laila (L) by Rahma Istiqomah, Immaah ... Immaaaahh (II) by Andi Indra Jaya, Air Mata Mayang from Ranah Betung (AMMdRB) by Mimi Artati, Aulia Azizah Boundary (TB), and Wayang for Nilam (WuN) by Dea Nada Fauzziah. Based on descriptive studies with repetitive reading techniques, it found some information about the value of children's character education related to intelligent, honest, caring, and resilient. The value of character education is in the groove and united in the narrative of the story. The theme of the seventh story is caring, persistence, and friendship. The story delivered by simple, straight forward, dialogue-style, and narrative.